2011
DOI: 10.1111/j.1600-0501.2011.02172.x
|View full text |Cite
|
Sign up to set email alerts
|

Early osseointegration to hydrophilic and hydrophobic implant surfaces in humans

Abstract: While healing showed similar characteristics with bone resorptive and appositional events for both SLActive and SLA surfaces between 7 and 42 days, the degree of osseointegration after 2 and 4 weeks was superior for the SLActive compared with the SLA surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
415
3
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 399 publications
(473 citation statements)
references
References 22 publications
48
415
3
7
Order By: Relevance
“…In this context, in vivo studies have shown that the SLActive surface is associated with an earlier onset of osseointegration 3,4) . As the biological processes of inflammation and bone formation have been shown to be inversely related during osseointegration 5) it can be reasonably suggested that the higher platelet activation associated with this surface could contribute to minimizing the inflammatory period through the enhanced recruitment and degranulation of neutrophils which would in turn speed up the onset of the healing/ osteogenic phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, in vivo studies have shown that the SLActive surface is associated with an earlier onset of osseointegration 3,4) . As the biological processes of inflammation and bone formation have been shown to be inversely related during osseointegration 5) it can be reasonably suggested that the higher platelet activation associated with this surface could contribute to minimizing the inflammatory period through the enhanced recruitment and degranulation of neutrophils which would in turn speed up the onset of the healing/ osteogenic phase.…”
Section: Discussionmentioning
confidence: 99%
“…Surface micro-roughness, such as that obtained in sand blasted and acid etched (SLA) implants, has been well recognized to promote osseointegration when compared with smoother surfaces 1) . Further modification of the SLA surface leading to increased hydrophilicity (SLActive), has been shown in recent human in vivo studies to be associated with even further acceleration of the onset of osseointegration 2,3) . However, the underlying biological mechanisms responsible for these observations have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…29 These experimental outcomes were confirmed not only by prospective clinical studies in which implants were loaded after 21 days of bone repair, 33,34 but also by studies measuring implant stability with the aid of resonance frequency analysis (RFA), 35 genetic expression profile and histological analysis of human models. 36,37 As regards the use of antibiotics, a recent systematic review concluded that scientific evidence suggests that, in general, this type of drug is advantageous, as it aids reducing failure rates of implants placed under normal conditions. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The samples were collected from five animals for each experimental period (7,14,21 and 28 days). The animals were maintained alive after biopsy.…”
Section: Histologic Specimens Preparation and Maintenance Of Animals mentioning
confidence: 99%
“…In this analysis, both implants tested are commercially available; however, regulators and professionals must have evidence that demonstrate the safety and efficacy of these products based on standardized protocols in order to reduce the use of inefficient products (6,14).…”
Section: Introductionmentioning
confidence: 99%